Pengembangan Rencana Pelaksanaan Pembelajaran Menggunakan Model Project Based Learning (PjBL) Pada Pembelajaran Tematik di Kelas IV SD Negeri Kota Bengkulu - Joko Prasetyo; Sri Dadi; Dwi Anggraini (JURIDIKDAS, 2020)
This research is motivated by the problem of the many teachers in elementary schools who have not implemented Thematic learning in the 2013 Curriculum properly. This study aims to produce a Learning Implementation Plan (RPP) using the Project Based Learning (PjBL) model in class IV Elementary Schools (SD) which can be used as a teacher's reference in implementing classroom learning. This research is a Research and Development (R&D) study by modifying the 4-D model by Thiagarajan and Sammel. However, this research was only carried out until the third stage, namely Develop. Validation is carried out by curriculum experts. The developed lesson plans were rated and responded by 8 elementary school teachers in Bengkulu City. Data analysis techniques used descriptive statistical analysis of the results of expert validation assessment and teacher responses and qualitative descriptive analysis of comments from expert validation and teacher responses. This study produced a Thematic Learning Implementation Plan (RPP) using the PjBL model with an assessment of curriculum experts at 95.63 with a very good category and a teacher response of 87.66 with an excellent category as the final product of development.